Ethics and corporate social responsibility in the meetings and events industry - Henderson, Elizabeth Anne; McIlwraith, Mariela (New Jersey : Wiley, 2013)
This title celebrates what has been already achieved in moving the meetings and events industry towards a more sustainable future, and pushes the boundaries of imagination to visualise what might be possible in the years to come! It includes a wealth of information on new sustainability tools.
Introduction to corporate social responsibility and ethics -- Business ethics and the meetings and events industry -- Strategies for sustainable meetings -- Social responsibility and culture -- Meetings, events, and environmental science -- Shared value and strategic corporate responsibility -- Communication, marketing, and public relations -- Sustainable supply chains for meetings and events -- Sustainability measurement and evaluation -- Sustainability reporting for meetings and events -- Risk management and legal considerations -- Backcasting and scenario planning for a sustainable meetings and events industry
Includes index.
Keywords: BUSINESS ETHICS